Chitty chitty bang bang [videorecording (DVD)] - Hughes, Ken, 1922-2001; Dahl, Roald; Jeffries, Lionel; Van Dyke, Dick; Howes, Sally Ann (Metro Goldwyn Mayer Home Entertainment, 2010)
An eccentric professor invents wacky machinery but can't seem to make ends meet. When he invents a revolutionary car, a foreign government becomes interested in it, and resorts to skulduggery to get their hands on it.